Sobre la presència de Boccaccio en el Curial e Güelfa: la novella X.8. - LLADÓS, SÒNIA GROS (Scripta, 2013)
The latest research on the Catalan chivalric novel Curial e Güelfa has highlighted unanimously the literary quality of the work and the richness of the literary culture of its author, in particular in relation to the classical and Italian writers. Among the Italians, many scholars have stressed the crucial role of Boccaccio, and in particular of the Decameron, as a literary model and as an intermediary in the classical tradition, for the anonymous Catalan author. In this work we offer a view of the presence of the novella X.8 in the Catalan text, following both narratives, and observing the fitting in the new narrative context that carries out the anonymous author of Curial. Besides, this allows us to appreciate the relationship of the chivalric novel and the Catalan translation of the Decameron of 1429.